The other Boston busing story : what's won and lost across the boundary line - Eaton, Susan E. (Brandeis University Press, 2020)
"METCO, America's longest-running voluntary school desegregation program, has for 34 years bused black children from Boston's city neighborhoods to predominantly white suburban schools. Sixty-five METCO graduates vividly recall their own stories in this revealing book. Susan E. Eaton interviewed program participants who are now adults, asking them to assess the benefits and hardships of crossing racial and class lines on their way to school. Their answers poignantly show that this type of racial integration is not easy-they struggled to negotiate both black and white worlds, often feeling fully accepted in neither. Even so, nearly all the participants believe the long-term gains outweighed the costs and would choose a similar program for their own children-though not without conditions and apprehensions"--